THE INFLUENCE OF NIEUWE BOUWEN ARCHITECTURE ON DUTCH COLONIAL BUILDING IN MEDAN CITY - Pane, Imam Faisal; A. Sianipar, Ribka (DIMENSI (Journal of Architecture and Built Environment), 2018)
Nieuwe Bouwen Architecture came and involved in Indonesia is carried by the young Dutch architects, also influenced Dutch colonial building in Indonesia to include Medan city. This study aims to determine what kind of Nieuwe Bouwen that control Dutch colonial buildings in Medan and find the form of the authority. This study used the qualitative method. There are 6 (six) aspects studied in this research that is the dynamic form; expressive ornaments; the building has a tower; nonstructural elements; glass, steel, and concrete materials; elements of air, light, and space. Analysis results show that PD Pasar Office Medan, Paradiso Swimming Pool, and Mandiri KC Medan City Hall Bank are influenced by Nieuwe Bouwen expressionism. Besides that, the form of expressionism on PD Pasar office Medan are of the curved shape of the building, unique, the expressive ventilation has the ornament and decorative element on its facade. As well as Paradiso swimming pool has curved shape, decoration and decorative element on its façade and tower. While at Mandiri KC Medan Cityhall bank, there is the geometric decoration, decorative element, and balcony also tower have expressive shape.